10 Conflicts to Watch in 2017 (International Crisis Group, 2017)
From Turkey to Mexico, the world s most volatile flashpoints will get a lot more unpredictable this year.
Keywords: Conflictos armados; Terrorismo internacional; Relaciones Internacionales; Prospectiva